Food Insecurity Among Students in Six Health Professions' Training Programs. Issue 4 (8th August 2021) - DeMunter, Jodi; Rdesinski, Rebecca; Vintro, Andrea; Carney, Patricia A.
Abstract : This study examines food insecurity in a novel population: health professions students. Their academic success has a unique impact on our nation's future health care system. We administered a 39-question survey, including open-ended questions that were coded for qualitative analyses, to 2, 853 students to delineate the scope of this problem and identify actionable solutions. The prevalence of food insecurity in this population is 28.5%, with one in five (21.3%) reporting lack of food impacting academic performance.